Urban form and economic sustainability in housing projects - Mohamed Mahmoud Ahmed Abdel Ghaffar (SpringerOpen, 2021)
Abstract Urban areas in metropolitan cities like Cairo suffer from economic, social, and environmental predicaments. Urban economic sustainability is an approach that reforms the urban performance to gain direct benefits such as minimizing costs and maximizing profits and indirect benefits as better social, environmental, and cultural aspects. This research suggests applying such an approach to enhance Egyptian housing projects. The main research question is how to evaluate the economic sustainability of urban forms?. The study presents a “Sustainable Urban Economy model” (SUE model) linking urban fabric, land use pattern, transportation, and street network design with economic sustainability. Research methods and tools include interviews (Delphi method) with 25 urban planning/design and urban economic experts to refine the model. Results show the most effective components of the urban form on economic sustainability (accessibility and degree of permeability, population density, built, and the impact of sub-indicators on the main components. Moreover, results indicate that the seven most influential indicators are the built-up to total space ratio, mixed-use ratio, built-up ratio, population density, floor area ratio, degree of accessibility, and public transportation. Experts suggested values for the seven indicators to measure how the urban form can achieve high economic, environmental, and social performance in the Egyptian context.